Towards an Interactive Agent-Based Approach to Real-Time Feedback (IAARF) in E-Learning System - Omoda-Onyait, Godfrey; Lubega, Jude T.; Maiga, Gilbert; Angole, Richard O. (Springer, Berlin, Heidelberg, 2012)
E-learning management systems use an interactive approach that presents the learner with learning objects to interact with during the learning process. Several interactive platforms for sharing learners’ ideas, integrating mutual knowledge or providing feedback have been proposed. However, these approaches have met with limited success. Furthermore, although design education is already taking full advantage of the current state and economy of online information, online teaching materials suffer from scanty content, poor interactivity, and insufficient participation. This paper proposes an interactive agent-based approach to real-time feedback (IAARF) generation in e-learning systems for higher institutions of learning. This approach presents the possible way to use agents in an interactive manner to create learner profiles, guide the learners to set the learning goals, learner activities, and extract learner resources during the learning process. The major strength of this approach is the high level of learner engagement, with real-time feedback (RF) to the learner, shaping and transforming their learning dynamics.
Keywords: Agent-oriented; e-learning; Interactive and real-time feedback